Anxiety Among Pregnant Women During Covid-19 Pandemic - Dina Zakiyyatul Fuadah (STIKes Patria Husada Blitar in collaboration with PPNI Kabupaten blitar, 2022)
Coronavirus disease 2019 (COVID-19) is a public health emergency of international concern and poses a threat to the mental health of pregnant women. There were 536 pregnant women exposed to Covid-19 in the April 2020-April 2021 period. As many as 20 percent of them died. The purpose of this study was to determine the correlation between social support and anxiety among pregnant women during the Covid-19 pandemic in Pare District, Kediri, East Java. The study was conducted from 9 to 21 March 2021. The data collection was on demographic data, anxiety, social support to COVID-19 of women with established medical records in the Community Health Center of Pare, District. Anxiety was assessed by the Pregnancy-Related Anxiety Questionnaire-revised (PRAQ-R2) questionnaire, social support was assessed by the Social Support Questionnaire. This study had 37 participants with most of them 20-30 years old. During the period of prevention and control of the epidemic, all the pregnant women adopted protective measures, such as wearing masks, washing hands frequently, and staying at home. The results of Social Support most pregnant (89.2) were in the high category and anxiety in pregnant the majority (64.9%) in the medium category. Analysis using the Spearman rank test, the results of p-value = 0.000 (< 0.05). The strength of the correlation between variables was indicated by the value of r = 0.570. Pregnant women's anxiety was affected by the readiness of pregnant women to face childbirth, knowledge of pregnant women, and level of education. It is hoped that pregnant women can manage their anxiety during the Covid-19 pandemic improving the quality of correlations with husbands and family members.